2014
DOI: 10.1155/2014/863482
|View full text |Cite
|
Sign up to set email alerts
|

Value of Histopathologic Examination of Uterine Products after First-Trimester Miscarriage

Abstract: The main rationale of routine histopathologic examination of products after first-trimester miscarriages is to detect an ectopic pregnancy or a molar pregnancy, which require further management. An alternative approach is to examine the products only when there is a definite indication. As there is no agreement, we aimed to study whether routine histopathological examination of tissues obtained after first-trimester miscarriage is of any clinical value in our populations. Medical records of all (558) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 11 publications
3
44
3
2
Order By: Relevance
“…5 The main role is to detect an ectopic pregnancy, which requires immediate further management, or a molar pregnancy, which needs special follow-up. 4 Other reasons include detecting surgical complications, such as incomplete evacuation after pregnancy failure; determining the cause of recurrent miscarriage; or detecting unexpected fetal pathology. 6 In addition from the Background and objective: Miscarriage represents a common problem that occurs in the first trimester of pregnancy.…”
mentioning
confidence: 99%
“…5 The main role is to detect an ectopic pregnancy, which requires immediate further management, or a molar pregnancy, which needs special follow-up. 4 Other reasons include detecting surgical complications, such as incomplete evacuation after pregnancy failure; determining the cause of recurrent miscarriage; or detecting unexpected fetal pathology. 6 In addition from the Background and objective: Miscarriage represents a common problem that occurs in the first trimester of pregnancy.…”
mentioning
confidence: 99%
“…Women who had faced problems related to logistics, women from rural residence, women who are unable to recognize their pregnancy early, and irregular nature of their menses were found to have an abortion in the second trimester period. As regards to item eleven which related to "Analgesia and sedation" the current study results showed that more than half of standards were competent achieved by all studied hospitals and there was highly significance differences among all studied hospitals regarding to standards (1,5,11,13,14,17,18). This results may be due to lack of hospitals resources& facilities and lack of health care provider's knowledge and experiences.…”
Section: Discussionmentioning
confidence: 65%
“…In agreement with previous studies the present study also has product of conception as the majority cases from those samples of spontaneous abortion. 10,11 Those studies were investigating the relation of histopathological findings with tissue samples obtained from first-trimester miscarriage, 11 and also exploring whether the routine histopathological examination is required to detect either an ectopic or molar pregnancy. 10,12 Moreover, the histopathological assessment has great value in the identification of different diseases compared to clinical and laboratory findings.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Those studies were investigating the relation of histopathological findings with tissue samples obtained from first-trimester miscarriage, 11 and also exploring whether the routine histopathological examination is required to detect either an ectopic or molar pregnancy. 10,12 Moreover, the histopathological assessment has great value in the identification of different diseases compared to clinical and laboratory findings. 12 The present study has revealed that inflammation and fibrin deposition are the major findings in the histopathological examination of decidua.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation